Green human resource management and brand citizenship behavior in the hotel industry: Mediation of organizational pride and individual green values as a moderator - Ibrahim A. Elshaer; Alaa M. S. Azazz; Chokri Kooli; Sameh Fayyad (Administrative Sciences, 2023)
In recent years, there has been growing awareness of the need for sustainability in the hospitality industry. The hotel industry, in particular, has been identified as a significant contributor to environmental degradation. To address this issue, hotel managers have begun to adopt green human resource management (GHRM) practices to promote sustainable behavior among employees. This research paper explores the relationship between GHRM practices, brand citizenship behavior (BCBs), organizational pride, and individual green values in the hotel industry. The study examines how GHRM practices influence BCB through the mediation of organizational pride and the moderation of individual green values. A survey was conducted with 328 employees from five-star hotels and the obtained data were analyzed using PLS-SEM. The results indicate that GHRM practices positively affect BCB and that this relationship is partially mediated by organizational pride. Furthermore, individual green values were found to moderate the relationship between GHRM practices and BCB, indicating that employees with stronger green values are more likely to exhibit BCB. These findings contribute to the literature on GHRM and BCB and offer insights for hotel managers on how to enhance their sustainability efforts through effective GHRM practices.
Keywords: 350; brand citizenship behavior; green human resources management; green management; green values; hotel industry; organizational pride; sustainable performance